2013
DOI: 10.1364/oe.21.014120
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric imaging of uterine cervix: a case study

Abstract: We present a preliminary investigation of macroscopic polarimetric imaging of uterine cervix. Orthogonal state contrast (OSC) images of healthy and anomalous cervices have been taken in vivo at 550 nm. Four ex vivo cervix samples have been studied in full Muller polarimetry, at 550 nm and 700 nm, and characterized in detail by standard pathology. One sample was totally healthy, another one carried CIN lesions at very early stage (CIN1) in its visible exocervical region, while for the other two samples more adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
156
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(173 citation statements)
references
References 23 publications
5
156
0
2
Order By: Relevance
“…Mueller matrix descriptions have been extended towards tissue autofluorescence spectroscopy and initially explored for cervical cancerous tissue diagnosis, as shown in Figure 2(e). The additional linear and cir- [12,21,22,164,167] cular diattenuation spectra possess potential advantages over elastic scattering based approaches. Contrast can be observed between normal and precancerous groups attributed to the loss of anisotropic organization of collagen, which suggests that fluorescence diattenuation and polarizance originating from anisotropic organization of collagen in the connective tissue may serve as potentially useful diagnostic metrics [167].…”
Section: The Biomedical Applications Of Mueller-polarimetric Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mueller matrix descriptions have been extended towards tissue autofluorescence spectroscopy and initially explored for cervical cancerous tissue diagnosis, as shown in Figure 2(e). The additional linear and cir- [12,21,22,164,167] cular diattenuation spectra possess potential advantages over elastic scattering based approaches. Contrast can be observed between normal and precancerous groups attributed to the loss of anisotropic organization of collagen, which suggests that fluorescence diattenuation and polarizance originating from anisotropic organization of collagen in the connective tissue may serve as potentially useful diagnostic metrics [167].…”
Section: The Biomedical Applications Of Mueller-polarimetric Imagingmentioning
confidence: 99%
“…The characteristic polarization information of interest is carried by a 4 3 4 matrix named a Mueller matrix and this can be experimentally obtained from Mueller polarimetry and polarimetric imaging. In recent years, an increasing number of biomedical applications of Mueller polarimetric imaging techniques have been proposed [5], e. g. oral cancerous legion detection [13], cervical cancer and colon cancer detection and staging [12,[14][15][16][17][18][19], assessment of cancer therapy [20], partial bladder obstruction diagnosis [21], guiding mass spectrometry for instant pathology [22], characterizing collagen fibres [23], and these have demonstrated advantages over polarization blind imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and MC simulated results have shown that the healthy cervix tissues are highly anisotropic [10,25]. However, anisotropy, as represented by retardance δ or the MMT parameter A, reduces significantly in the cancerous regions.…”
Section: Cancerous Tissue Samplesmentioning
confidence: 99%
“…Some of the linear polarization imaging methods have even been combined with endoscopes for in vivo diagnostic purposes [8,9]. Since a Mueller matrix provides a comprehensive characterization of the polarization properties and contains abundant microstructural and optical information of the sample, imaging methods based on Mueller matrix polarimetry are becoming increasingly attractive for differentiating the pathological structural features of biological samples, such as different types of cancers at different stages [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature shows that more than 85% of cancers originate from the superficial epithelium, which means that polarization imaging methods have great potential in screening and identifying cancer at an early stage [19,20]. Therefore, Mueller matrix polarimetry has been used to assist the diagnosis of various cancerous tissues, such as skin cancer [21], cervical cancer [22], colon cancer [23], liver cancer [24,25], and so on [26,27]. Recently, we have designed a Mueller matrix microscope by adding a polarization state generator and analyzer (PSG and PSA) to a commercial transmission-light microscope and applied it to detect human liver and cervical cancerous tissues with fibrosis [24,25].…”
Section: Introductionmentioning
confidence: 99%